Indonesian Pythochemical as Erythropoietin Agonist In Sillico to Treatment Anemia in Chronic Kidney Disease - Kamil, Muhammad Rizki; Suselo, Yuliana Heri; Wulandari, R. Aj Sri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: Anemia is the most frequent complication in CKD and until now the its treatment still hampered effectiveness and efficiency. Indonesia is known to have 9,600 species of plants that have a pharmacological effect and some compounds have been created for 3D structures and databases. Molecular docking is beginning of the process of the invention the drug most widely used. This study aims to screen Indonesian herbal plant that has activity as an agonist of erythropoietin receptor for treatment of anemia in CKD development with molecular docking method. Methods: The research was a bioinformatics study which utilized all phytochemicals in HerbalDB that had PubChem access code and met the criteria for Lipinskis rule of five as sample. The complex of Epo-EpoR was obtained from the Protein Data Bank, code: 1CN4. Validation of truncated Epo with EpoR needed to get docking scores and binding site at EpoR. Molecular docking between phytochemical compounds with EpoR models was done using AutodockVina 1.1.2. Visualization of docking results was done using PyMOL 1.7.4. Results: There are 12 phytochemicals that have 10 of 17 in common EpoR binding site. There are seven of them met the criteria phytochemical Lipniskis rule of five and then two phytochemicals are selected which has the most variation binding site to EpoR, 18 sites. GibberellinÂ A51 and Miraxanthin-III were two selected phytochemicals of the most potentially as EpoR agonist based on analysis of docking scores, binding site similarity with truncated Epo, and Lipinskis rule of five criterias. Conclussion: GibberellinÂ A51 and Miraxanthin-III were the most potent Indonesian phytochemicals that could be a EpoR agonist to development of treatment anemia in CKD. Keywords: Anemia, CKD, EpoR agonists, Indonesian phytochemicals, molecular docking